An Overview of Cyber Security in Digital Banking Sector - Chandra sekhar; Manojkumar Kumar (East Asian Journal of Multidisciplinary Research, 2023)
In the 21st century the online technology as updated with high performance and used widely by all users. In top five the Digital Banking Sector is also one which makes use of online  technology constantly such as NEFT, Googlepay, Phonepe etc. Though there are more usage of Online banking but still the cybercrime in the banking sector has been increasing over the years. As reported 50% of cybercrime is happened related to ATM, debit card and net banking. Banking sector is facing cyber attacks more times compared to other sectors. This paper view the cyber attacks in the banking sector and way of providing the cyber security to those attacks.